ANALISIS PENGARUH PINJAMAN DANA BERGULIR PNPM MANDIRI TERHADAP PENDAPATAN MASYARAKAT MISKIN DI KECAMATAN SIULAK KABUPATEN KERINCI - Hastin, Mira (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to analyze the Analysis of the Effect of Rolling Fund Loans National Program for Community Empowerment (PNPM) on the Income of the Poor District of Siulak. This study uses questionnaire data from PNPM borrowers in Siulak District. The types of data used are primary data and secondary data. Data analysis using quantitative and qualitative descriptive statistics, simple regression analysis test. The variables used in this study are the Revolving National Community Empowerment Program (PNPM) as an independent variable; and the income of the poor in the Siulak sub-district as the dependent variable.The results of this study indicate that the Revolving Fund National Program for Community Empowerment (PNPM) has a significant effect on the income of the poor in the Siulak District.